Distribution of soil morphology and physicochemical properties to assess the evaluation of soil fertility status using soil fertility capability classification in North Galela, Indonesia - Tri Mulya Hartati; Bambang Hendro Sunarminto; Sri Nuryani Hidayah Utami; Benito Heru Purwanto; Makruf Nurudin; Krishna Aji (Brawijaya University, 2023)
One of the indicators of land productivity assessment is soil fertility. The causes of infertile soil have been widely reported. This study aimed to evaluate soil fertility using the Soil Fertility Capability Classification (SFCC) approach and to determine the relationship between soil morphological and physiochemical properties and soil fertility. The research was conducted in North Galela Sub-district, North Halmahera Regency. The research framework began with the interpretation of thematic maps, surveys, field observations, and the making of soil fertility evaluation maps. Soil sampling was carried out based on the stratified random sampling method and supported by laboratory measurements according to USDA international standards. The research result showed that the research area had 14 soil fertility statuses. The fertility classes having the most significant limiting factor were loamy texture (Ø<0.002 mm), rock surface, gravel subsoil, moderate salinity (0.2-0.4 mS cm-1), low exchangeable K (<20 cmol(+) kg-1), and sloping slope (8%) with Lithic Haprendolls type and loamy texture (Ø<0.002 mm), subsoil >15% rock outcrop, moderate salinity (0.2-0,4 mS cm-1), Na saturation >15%, and a rather steep slope (14%) with Lithic Eutrudepts type. Both of these classes have a top layer texture, and the bottom layer contains clay <35%, with limiting factors of hard layer inhibiting root to a depth of 50 cm, extremely low nutrient reserve, low electrical conductivity (EC) and high Na. The limiting factors found in North Galela Sub-district were hard root-restricting layer, exchangeable K, electrical conductivity, Na saturation, slope, and gravel.